Structured BASIC - Clark, James F.; Drum, William O. (Cincinnati, Ohio : South-Western Publishing Co., 1983)
Computers have become indispensable tools for businesses, professional, people and government. Computer programming ability has thus become vastly more important, both as a career opportunity and for personal use. The advent of microcomputer has resulted in a literal explosion of computers using the BASIC language.
Chapter 1. Getting started in basic -- Chapter 2. Doing arithmetic and designing programs -- Chapter 3. Using read and data statements -- Chapter 4. Improving the appearance of printed reports -- Chapter 5. Designing interactive programs -- Chapter 6. Summarizing -- Chapter 7. Subtotals and group printing -- Chapter 8. Writing programs in easy-to-Understand modules -- Chapter 9. Using controlled loops -- Chapter 10. Tables --Chapter 11. Sorting -- Chapter 12. Advanced handling of character data --Chapter 13. Sequential data files -- Chapter 14. Random data files -- Glossary -- Appendixes.
Keywords: BASIC (PROGRAMMING LANGUAGE); COMPUTING -- PROGRAMMING LANGUAGE -- BASIC